Sea-cliff Erosion with Rising Sea-Level along Shores Exposing Glacial Material in Atlantic Canada: The Effect of Bedrock Slope and an Example from Isle Madame, Nova Scotia - Force, Eric R. (Geoscience Canada, 2013)
Rapid retreat rates of sea cliffs exposing glacial material are a widespread problem, especially in Atlantic Canada, and one that will continue. Prediction of retreat rates at specific sites involves many variables, but a factor that has commonly been overlooked in such prediction is the slope of the bedrock surface under the glacial material. A glaciated bedrock platform is generally necessary to establish a stable situation of temporary equilibrium, and as sea-level rises, the bedrock slope determines the location of the new equilibrium position. An example from Nova Scotia shows that bedrock slope is so low on some coasts that the only long-range limiting factor is kinetic, i.e. how fast hydrodynamic energy can remove glacial material. Prediction of coastal retreat scenarios requires better information on the bedrock surface than is commonly available. SOMMAIRE Les taux de retrait rapide des falaises qui exposent des matériaux glaciaires est un problème très répandu et qui va perdurer, surtout dans le Canada atlantique. La prévision des taux de retrait sur des sites spécifiques comporte de nombreuses variables et, la pente du substratum rocheux sur lequel reposent ces matériaux glaciaires et une variable qui a souvent été négligée. L’existence d’un substratum rocheux glacié est généralement une condition nécessaire pour l’établissement d’une situation d'équilibre stable temporaire, et lorsque le niveau de la mer monte, la pente du substratum rocheux a une influence déterminante sur le lieu de la nouvelle position d'équilibre. Un exemple en Nouvelle-Écosse montre que la pente du substratum rocheux est si faible sur certaines côtes que le seul facteur déterminant à long terme est la cinétique, c'est-à-dire la vitesse d’abrasion du matériau glaciaire correspondant à l’énergie hydrodynamique. La prévision des scénarios de retrait de la ligne côtière requière une meilleure connaissance du substratum rocheux.